(untitled) (Jóvenes en la Ciencia, 2017)
Aspergillus niger var tubingensis naturally produces the enzyme glucose oxidase. In previous studies it was discovered that the Ed8 strain is doing that remarkably well compared to other strains and microorganisms. As a continuation to these investigations, experiments with Ed8 had been done in a larger scale. The experiments show a high dependency of GOX production on aeration. Where in the small scale of 50 mL working volume (as used in previous studies) the specific oxygen transfer is sufficient, one has to use active aeration at higher working volumes. Also important is the agitation or more specifically the power entry per volume which affects the size of the Ed8 agglomerates. The agitation in the Airlift reactor seems not to be sufficient to effectively grow the Ed8 microorganism. To run the fermentation system on a large scale, one has to find the best parameter set of agitation and aeration to achieve as much and as small Ed8 agglomerates as possible.